New Perspectives in Individualized Instruction - H. James Funk; L. James Walter (Educational Considerations, 1975)
Individualization is only a point on a continuum between totally teacher-directed instruction and totally student-determined learning. The variables and the extent of individualization are manipulated to fit student outcomes.